PENGARUH IKLIM ORGANISASI SEKOLAH TERHADAP KOMITMEN GURU SEKOLAH MENENGAH PERTAMA DI KECAMATAN PONJONG KABUPATEN GUNUNGKIDUL - , Nurdhani Dharianta ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Smallest school is a subsystem of the national education system, the national educational success depends on the success of education in schools. As a school system must empower all the components in it to work effectively and efficiently. Components that affect the school are internal and external components. Internal components include inputs, processes, outputs and outcomes expected running well and support each other so as to create a school climate that is conducive to the process. External components which take effect on the climate of the school is the support of government, society, science and technology advances, the demands of globalization, and the demands of self-development. The purpose of this study was to examine the influence of school organizational climate which consists of four dimensions of the commitment of junior high school teachers in the Kecamatan Ponjong Kabupaten Gunungkidul either partially or simultanously. Based on the utilization of this research can be classified as applied research with a deductive approach. If viewed from the goal of this research study is classified as explanatory research. On explanatory research aims to uncover the relationship between the variables and testing the theory. Population of this study were secondary school teachers in the Kecamatan Ponjong. While the method of determining the sample is done by non-random sampling is purposive sampling whereas the samples used were 96 junior high school teachers are civil servants in the Kecamatan Ponjong. Results from this study is that there is influence between organizational climate schools with teachers' commitment. If we see the influence of each dimensions of the organizational climate are collegial leadership, achievement press, and institutional vurnerability had no effect while the professionalism of teachers has a significant influence on teachers' commitment.